Changes in Variability and Flexibility of Individual Travel in Germany: Trends and Drivers. Issue 1 (January 2015) - Streit, Tatjana; Allier, Charles-Elie; Weiss, Christine; Chlond, Bastian; Vortisch, Peter
Are daily life and daily travel behavior in Germany more flexible today than it was 10 to 15 years ago? Against the background of an increasing use of information and communication technologies (ICT) and the question of that impact on daily life, this paper analyzes changes in the variability of travel behavior. The paper examines the data from individual travel diaries of a whole week covering a longitudinal perspective over 15 years. These two dimensions of information allow for more detailed evaluation of variability profiles. The analyses were based on traditional key values of daily travel as well as new customized measures of individual variability in travel behavior in the course of a whole week. The paper investigated the temporal development by sociodemographic group. The results show that travel behavior patterns of young men and woman in Germany are becoming more similar. The young age group drives several trends, including multimodality. However, at the same time, young men are shifting their leisure habits toward more home-located activities; this effect is possibly partly induced by the influence of ICT.